Pengaruh Keterampilan Membaca Pemahaman Melalui Strategi Directed Reading Thinking Activity (DRTA) Berbantu Media Gambar Berseri Kelas V SDN Sudimara 13 Kota Tangerang - Ina Magdalena; Nur Amalia Fajriah; Siti Kurniani Ningsih; Sri Melani (Jurnal Halaqah, 2020)
This research aims to determine the significant influence of reading comprehension skills between groups of students who are taught by using a learning strategy Directed Reading Thinking Activity (DRTA) assisted by serial image media and groups of students who do not use a learning strategy Directed Reading Thinking Activity (DRTA) assisted by serial image media in fifth-grade students at Sudimara 13 Elementary School Academic Year 2020/2021. This research is a quasi-experimental with a non-equivalent post-test only control group design. The research sample consisted of 51 students, consisting of 23 students of the VA class as the experimental group and 28 students of the VB grade as the control group. The sample selection uses a random sampling technique. Data on reading comprehension skills were collected using instruments in the form of multiple-choice tests. Data analysis uses descriptive statistical analysis and inferential statistical analysis (t-test). The results showed that tcount > ttable (tcount 5, 57 > ttable 1, 70). Based on the results of the study it can be concluded that there are significant differences in students' reading comprehension skills that are learned by using Directed Reading Thinking Activity (DRTA) learning strategies assisted by serial images media and students who are not taught by using Directed Reading Thinking Activity (DRTA) learning strategies assisted with image media beamed in class V at SDN Sudimara 13 in Academic Year 2020/2021.